Early vascular damage in retinal microcirculation in arterial hypertension: the Czech post-MONICA study - Cífková, Renata; Harazny, Joanna M; Bruthans, Jan; Wohlfahrt, Peter; Krajčoviechová, Alena Hrubeš; Lánská, Věra; Gelžinský, Július; Mateřánková, Markéta; Mareš, Štěpán; Filipovský, Jan; Mayer, Otto; Schmieder, Roland E (Journal of hypertension, 2024)
UNLABELLED: Retinal microcirculation reflects retinal perfusion abnormalities and retinal arterial structural changes at relatively early stages of various cardiovascular diseases. Wall-to-lumen ratio (WLR) may represent the earliest step in hypertension-mediated organ damage.Our objective was to compare functional and structural parameters of retinal microcirculation in a randomly selected urban population sample, in hypertensive and normotensive individuals. DESIGN AND METHOD: A total of 398 randomly selected individuals from an urban population aged 25-65 years, residing in Pilsen, Czech Republic, were screened for major cardiovascular risk factors. Retinal microcirculation was assessed using scanning laser Doppler flowmetry, with data evaluable in 343 patients. Complete data were available for 342 individuals divided into four groups based on blood pressure and control status of hypertension: normotensive individuals ( n = 213), treated controlled hypertensive individuals ( n = 30), treated uncontrolled hypertensive individuals ( n = 26), and newly detected/untreated hypertensive individuals ( n = 73). RESULTS: There was a tendency to higher wall thickness in treated but uncontrolled hypertensive patients (compared to normotensive and treated controlled hypertensive individuals). WLR was significantly increased in treated but uncontrolled hypertensive patients as well as in individuals with newly detected thus untreated hypertension or in patients with known but untreated hypertension. There was no difference in WLR in treated, controlled hypertensive patients compared with normotensive individuals. CONCLUSION: Our results show that an increased WLR, reflecting early vascular damage, was found in newly detected individuals with hypertension and in untreated hypertensive patients, reflecting early hypertension-mediated vascular damage. Early initiation of hypertension treatment may be warranted.
Keywords: hypertenze; arterioly; Czech Republic; Retinal Vessels; Blood Pressure; Česká republika; mikrocirkulace; Hypertension; Microcirculation; Humans; lidé; krevní tlak; retinální cévy; Arterioles